EXCLUSIVE BREAST FEEDING RELATIONSHIP WITH INCIDENCE OF STUNTING IN CHILDREN AGED 2-3 YEARS AT PUSKESMAS PEMARON BREBES - Zahrotun Nisa' Setyoputri (Journal of Applied Health Management and Technology, 2022)
The 2020 Basic Health Research noted that the national stunting prevalence reached 37.2 percent, an increase from 2018 (35.6%). stunting also tends to be more susceptible to infectious diseases, so they are at risk of experiencing a decrease in the quality of learning at school and are at risk of being absent more often. Stunting also increases the risk of obesity, which continues for a long time and will increase the risk of degenerative diseases. Several factors that are thought to be the risk of stunting in children, one of which is exclusive breastfeeding. Reports at Pemaron Health Center in 2020 of 979 toddlers (61.5%) in the short and very short categories 53 toddlers (5.41%). The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of stunting in children aged 2-3 years. Quantitative research method , time approach using cross sectional method . The population in this study were all mothers of toddlers and children aged 2-3 years who experienced stunting totaling 49 toddlers, the sample was taken by proportionate stratified random sampling. The results of the study are Children age 2-3 years mostly given exclusive breastfeeding. Toddler 2-3 years most of the respondents are in the short category. There is a relationship between exclusive breastfeeding and the incidence of stunting in children 2-3 years. Conclusion There is a relationship between exclusive breastfeeding and the incidence of stunting in children 2-3 years old.